The increasing importance of the gut microbiome in acne vulgaris - Siddiqui, Ruqaiyyah; Makhlouf, Zinb; Khan, Naveed Ahmed (Folia microbiologica, 2022)
Acne is a frequently presented dermatological condition brought about by an interplay among inflammation, increased sebum production, hyperkeratinisation, and predominantly Propionibacterium acnes (renamed as Cutibacterium acnes) proliferation, leading to debilitating psychological scars. However, it has been shown that it is the loss of microbial diversity in the skin and the imbalance among C. acnes phylotypes that brings about acne rather than the C. acnes species as a whole. Interestingly, recent evidence suggests that other microorganisms may be implicated, such as the fungi Malassezia and the bacteria Cutibacterium granulosum. A plethora of scientific evidence suggests that the gut microbiome is implicated in the overall health and physiology of the host; studies show that the gut microbiome of acne patients is distinct and depicts less microbial diversity compared to individuals without acne. Herein, using the key terms: acne, C. acnes, IGF-1, sebum, and gut microbiome, we carried out a review of the literature, using Google Scholar and PubMed, and discussed the role of the gut and skin microbiome in relation to acne, as a narrative review. The role of hormones, diet, sebum, and stress in relation to the gut microbiome was also investigated. Therapeutic implications and the use of pre-/postbiotics are also deliberated upon. In this light, future research should investigate the relationship between the gut microbiome and the agreed upon factors of acne pathology, potentially leading to the discovery of novel acne treatments with milder side effects.
Keywords: střevní mikroflóra; mikrobiota; acne vulgaris; kůže; Skin; lidé; Cutibacterium acnes; Acne Vulgaris; Probiotics; Propionibacterium acnes; Skin microbiome; Gastrointestinal Microbiome; Humans; Microbiota; Gut microbiome